2020
DOI: 10.7150/jca.36372
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin in combination with JS-K inhibits growth of renal cell carcinoma cells via reactive oxygen species activation and inducing DNA breaks

Abstract: Metformin (MET) is taken as a principal medication for remedying Type 2 diabetes mellitus. Its anti-tumor effect has been reported increasingly, but the precise mechanism of it remains unclear. This study aims to explore the efficacy of MET and MET combined with nitric oxide donor prodrug JS-K on the proliferation, apoptosis, and DNA damage in human renal cell carcinoma (RCC) cells, and investigate the possible molecular mechanism involved. The cell proliferation was tested through methyl-tetrazolium assay and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…We speculated that synergistic killing-effect in our study was due to Met providing ROS or RNS to CAP, enhancing the CAP-associated cell death. Although Met has been reported as an antioxidant regent in diabetic patients [36], there was research suggested Met increased intracellular ROS [37]. The radical (OH or O 2 -) induced oxidation byproducts of metformin did not contain ROS and RNS [38], this means that the interaction between CAP and Met may not contribute to the synergistically inhibitory effect.…”
Section: Discussionmentioning
confidence: 97%
“…We speculated that synergistic killing-effect in our study was due to Met providing ROS or RNS to CAP, enhancing the CAP-associated cell death. Although Met has been reported as an antioxidant regent in diabetic patients [36], there was research suggested Met increased intracellular ROS [37]. The radical (OH or O 2 -) induced oxidation byproducts of metformin did not contain ROS and RNS [38], this means that the interaction between CAP and Met may not contribute to the synergistically inhibitory effect.…”
Section: Discussionmentioning
confidence: 97%
“…In colon cancer cells, the antidiabetic drug, combined with cisplatin, inhibited cell viability, decreased colony formation, and induced the intrinsic apoptosis pathway through increased ROS-mediated PI3K/Akt signaling pathway activity [302]. In lung cancer cells, by means of in vitro and in vivo studies, it has been shown that metformin, in combination with celecoxib, induces ROS aggregation, leading to mitochondrial membrane potential alteration, DNA double-strand breaks and increased expression of the tumor suppressor factor p53, causing cell cycle arrest and cell proliferation inhibition [303]; similar mechanisms were reported to mediate the antitumor activity of metformin, in combination with standard therapies, in different types of cancer cells [304][305][306][307].…”
Section: Targeting Mitochondrial Functional and Structural Dynamicsmentioning
confidence: 90%
“…Metformin was already shown to successfully prevent cancer cell viability and cell proliferation by inducing G 2 /M cell cycle arrest in a dose and time-dependent fashion followed by programmed cell death induction, effects that were attributed to increased ROS levels [68]. Likewise metformin targeted mitochondria-dependent apoptosis, and inducing DNA breaks by activating ROS [71]. Moreover, ROS levels vary during cell cycle progression and peak in mitosis.…”
Section: Discussionmentioning
confidence: 99%